Association between Aβ and tau accumulations and their influence on clinical features in aging and Alzheimer's disease spectrum brains: A [11C]PBB3‐PET study. Issue 1 (22nd December 2016) - Shimada, Hitoshi; Kitamura, Soichiro; Shinotoh, Hitoshi; Endo, Hironobu; Niwa, Fumitoshi; Hirano, Shigeki; Kimura, Yasuyuki; Zhang, Ming‐Rong; Kuwabara, Satoshi; Suhara, Tetsuya; Higuchi, Makoto
Abstract: Introduction: Amyloid‐β (Aβ) and tau accumulations may occur independently and concurrently as exemplified by primary age‐related tauopathy and Alzheimer's disease (AD), respectively. Interactions between Aβ and tau accumulations and their influence on clinical features, however, are still unclear. Methods: Associations among clinical symptoms, gray‐matter volume, regional tau, and Aβ deposition assessed by positron emission tomography with [ 11 C]pyridinyl‐butadienyl‐benzothiazole 3 (PBB3) and [ 11 C]Pittsburgh compound‐B (PiB), were evaluated in 17 AD, 9 mild cognitive impairment due to AD, and 28 PiB(−)‐cognitive healthy controls (HCs). Results: High tau burden was associated with aging and low‐level education in PiB(−)‐HC and AD‐spectrum groups, and with high Aβ burden and low‐level education in all subjects. It was not Aβ but tau accumulation that showed significant associations with cognitive performance even in PiB(−)‐HC. Discussion: The present study indicated aging and low‐level education after Aβ would be enhancers for tau pathology, associated with neurodegeneration and cognitive impairment in healthy and diseased elderly individuals.